Influência do método de filetagem e categorias de peso sobre rendimento de carcaça, filé e pele da tilápia do Nilo (Oreochromis niloticus) - de Souza, MLR; Macedo-Viegas, E. M.; Kronka, S. D. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1999)
The objective of this study was to evaluate the processing methods (F-1 = to remove skin with pliers and then to cut in fillets; F-2 = cut in fillet and then to remove skin with knife and pliers help) and weight categories (W-1=250-300 g; W-2=301-350 g; W-3 = 351-400 g and W-4 = 401-450 g), on the carcass (CY), fillet (FY) and skin yield of Nile tilapia. Forty-eight fishes were used in a completely randomized design. There was effect for the processing method, being the F-1 mean (56.43 and 36.67 %) higher to the F-2 (53.46 and 32.89%) for CY and FY respectively. For the weight categories, W-1 (56.49 and 37.34%) and W-2 (56.34 and 36.40%) were superior as compared to W-3 (53.27 and 31.98%) and W-4 (53.71 and 33.42%), respectively for CY and FY. Crude skin percentage, clean and of fleshed were higher for F-2, but there was no effect for weight categories. The F-1 processing method promoted the best yield and skin results, and for the weight categories W-1 and W-2 higher yields.
Influence of processing method and weight categories on carcass, fillet and skin yield of Nile Tilapia (Oreochromis niloticus)
Keywords: Oreochromis niloticus; fish production; fish processing; fillet processing; Nile Tilapia